Mergers and Acquisitions and wage effects in the Portuguese banking sector - Carvalho, Margarita Arantes Salgueiro de (2019)
This study examines the impacts of mergers and acquisitions (hereafter M&A) on wages of workers for the period 1993-2007. The results suggest a positive effect of M&A on wages; however, for workers that have participated in M&A in an acquired bank, it seems that M&A has a detrimental impact reflected by a reduction of the positive effect. We have also observed that the effects of acquisitions differ over time indicating that time dimension is an important element to consider, as the positive effect is not so manifest in the second year after the M&A; moreover we observe that the positive effect decreases even more in the third year after the M&A. The research also tries to assess if the effects differ according to the M&A type and the worker qualification level. Empirical results show that for highly qualified workers, M&A seems to be positive for wages. M&A may also produce different effects on employees’ wages according to the type of operation. Domestic acquisitions tend to have a positive effect on wages, but when analysing the impact on workers of foreign acquisitions, the results show a negative effect.